The Semantic-Functional Variety of the Lithuanian Mental Verbs manyti ‘Think’ and suprasti ‘Understand’ - Liauksminienė, Justina (Verbum, 2025)
The article explores the syntactic and semantic-functional variation of two Lithuanian mental verbs manyti ‘think’ and suprasti ‘understand’ in contemporary Lithuanian by showing how these verbs have been affected by the semantic changes of (inter)subjectification and pragmaticalisation. The aim is to identify which forms of the verbs, specifically 1st, 2nd person singular and plural verb forms, imperative forms or non-agreeing participles, display the traces of these semantic changes. The data were drawn from the Corpus of Contemporary Lithuanian Language and the database of spoken Lithuanian Kalba Vilnius. The qualificational meaning of the mental verbs under analysis correlates with their complement taking predicate (CTP) usage and shows that CTPs controlling a kad / jog ‘that’ complement clause are undergoing the semantic change of (inter)subjectification. The qualificational meaning of these verbs no longer marks the process of thinking and understanding, as found in their non-qualificational meaning, but rather denotes the evaluation of the proposition in terms of the sources of knowledge or likelihood (epistemicity). The further development of manyti ‘think’ and suprasti ‘understand’ in the process of (inter)subjectification is marked by their qualificational meaning that correlates with their parenthetical CTP use. This development results in the pragmaticalisation of mental verbs, which is evidenced by their adverbial distribution, structural changes and pragmatic meanings. Although the verbs manyti ‘think’ and suprasti ‘understand’ in their qualificational meaning are more prevalent in spoken discourse, the prevalence of their non-qualificational meaning in written discourse confirms that these mental verbs are still in the ongoing process of structural and semantic-functional change.
Keywords: mental verbs; (non)qualificational meaning; pragmaticalisation; (inter)subjectification